Molecular Identification and Diversity of 'Candidatus Phytoplasma solani' Associated with Red‐leaf Disease of Salvia miltiorrhiza in China. Issue 11 (8th August 2016) - Yang, Ruihuan; Wang, Guiwei; Wang, Sai; Zhang, Di; Wei, Liangzhu; Chen, Haimin; Li, Ou; Hu, Xiufang
Abstract: Reddening disease has recently been threatening Salvia miltiorrhiza in China, ranging from 30 to 50%. The main symptoms observed, such as plant stunting, inflorescence malformation, leaf reddening, fibrous roots browning, skin blackening and eventually root rot, are typically associated with phytoplasma infection. The presence of phytoplasmas was demonstrated through phytoplasma‐specific PCR, with the expected amplification (1.8 kb) from symptomatic S. miltiorrhiza plants from Shangluo, Shangzhou and Luonan fields in Shaanxi Province of China. The sequences of 16S rRNA, tuf, sec Y and vmp 1 genes amplified from LN‐1 phytoplasma shared the closest homologies of 99%, 100%, 99% and 98% with those of the reference strain Candidatus Phytoplasma solani (subgroup 16SrXII‐A), respectively. The phylogenetic trees showed that LN‐1 phytoplasma clustered with the members of 16SrXII‐A group, including Ca .  P. solani . Computer‐simulated restriction fragment length polymorphism analysis further supported this classification. Diversity analysis showed that all ' Ca .  P. solani ' strains identified from the three different regions examined shared 100% identical 16S rRNA, tuf, sec Y and vmp 1 nucleotide sequences. To the best of our knowledge, this is the first report of phytoplasma infecting the medicinal plant of S. miltiorrhiza . The results demonstrate that ' Ca .  P. solani ' is the presumptive aetiological agent of S. miltiorrhiza reddening disease in China.